2020
DOI: 10.1111/jcmm.16169
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LETM1 inhibits the proliferation and stemness of colorectal cancer cells through reactive oxygen species–induced autophagy

Abstract: Leucine zipper‐EF‐hand–containing transmembrane protein 1 (LETM1) is a mitochondrial inner membrane protein that is highly expressed in various cancers. Although LETM1 is known to be associated with poor prognosis in colorectal cancer (CRC), its roles in autophagic cell death in CRC have not been explored. In this study, we examined the mechanisms through which LETM1 mediates autophagy in CRC. Our results showed that LETM1 was highly expressed in CRC tissues and that down‐regulation of LETM1 inhibited cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…AMPK inhibition would lead to deregulation of the normal progression of the cell cycle. Accordingly, LETM1-KD reduced the expression of cancer stemness-related genes, increased AMPK activation, arrested cell cycle, lowered the number and size of tumor spheroids, and markedly inhibited cell proliferation (Che et al, 2020;Li et al, 2020;Piao et al, 2020).…”
Section: Letm1 In Cancermentioning
confidence: 97%
“…AMPK inhibition would lead to deregulation of the normal progression of the cell cycle. Accordingly, LETM1-KD reduced the expression of cancer stemness-related genes, increased AMPK activation, arrested cell cycle, lowered the number and size of tumor spheroids, and markedly inhibited cell proliferation (Che et al, 2020;Li et al, 2020;Piao et al, 2020).…”
Section: Letm1 In Cancermentioning
confidence: 97%
“…It is worth mentioning that the down-regulation of LETM1 induced autophagy in colorectal cancer (CRC) cells, and the autophagy inhibitor 3-methyladenine reversed the inhibitory effects of LETM1 silencing on proliferation and stemness. A further analysis indicated that the suppression of LETM1 increased the levels of reactive oxygen species (ROS) and mitochondrial ROS, activated the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) and, thus, initiated autolysis [ 38 ]. In our current study, the LETM1 protein was significantly suppressed, and the AMPK pathway was promoted in the AP (autolysis) group, compared to the AXP (non-autolysis) group, indicating that the suppression of LETM1 induced the AMPK pathway and initiated autolysis in P. pastoris .…”
Section: Resultsmentioning
confidence: 99%
“…Some of these proteins, including OCT4, MYC, KLF4, and SOX2 (Yamanaka factors), are universal, considering that they are typical of both cancer and normal stem cells and are considered essential for stem-related phenotypes [ 107 ]. The regulation of other markers, though, for instance, NANOG, BMI-1, SNAIL, ALDHs, LGR5, CXCR4, REX-1, Musashi-1, LETM1, and C-met, is considered to be dependent on both the cancer type and the specific phenotype of the CSCs that we want to analyze (e.g., drug-resistant, tumorigenic, metastatic) [ 35 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Studying the expression of specific genes both at the transcriptional and translation level, as well as the activity and localization of these proteins, is useful in assessing the enrichment of CSC properties [ 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%